Risk of hepatocellular carcinoma among individuals with different aetiologies of cirrhosis: a population-based cohort study - West, Joe; Card, Timothy R.; Aithal, Guruprasad P.; Fleming, Kate M. (Wiley, 2017)
Background: Among patients with cirrhosis, only those determined to be at risk for hepatocellular carcinoma (HCC) should undergo surveillance. However, little is known about how different aetiologies of cirrhosis affect risk for HCC. Aim: To quantify the cumulative incidence of HCC among a representative population of people with cirrhosis of the liver of varying aetiology. Methods: We identified subjects with hepatic cirrhosis from the UK's General Practice Research Database (1987-2006). Diagnoses of HCC were obtained from linked national cancer registries (1971-2006). Cox proportional hazards regression was used to estimate hazard ratios. The predicted 10-year cumulative incidence of HCC for each aetiology of cirrhosis was estimated while accounting for competing risks of death from any cause and liver transplant. Results: Among 3107 people with cirrhosis the adjusted relative risk of HCC was increased 2- to 3-fold among people with viral and autoimmune/metabolic aetiologies, compared to those with alcohol-associated cirrhosis. The 10-year predicted cumulative incidence estimates of HCC for each aetiology were: alcohol, 1.2%; chronic viral hepatitis 4.0%; autoimmune or metabolic disease 3.2%; and cryptogenic 1.1%. Conclusions: In a population-based study in the UK, people with cirrhosis have an estimated cumulative 10-year incidence of HCC of 4% or lower. Cumulative incidence varies with aetiology such that individuals with alcohol or cryptogenic cirrhosis have the lowest risk for Risk of HCC in cirrhosis HCC. These findings provide important information for cost-effectiveness analyses of HCC surveillance.